MEMBERIKAN PELATIHAN MICROSOFT OFFICE POWERPOINT MELALUI APLIKASI ZOOM DITENGAH PANDEMI COVID-19 BAGI SISWA MADRASAH TSANAWIYAH - Ahmad Nurdin Hasibuan; Marsadi Aras; E. Taufik Rahmat (Lembaga Penelitian Dan Pengabdian Pada Masyarakat (LPPM) Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2021)
The shift of conventional learning systems to online systems is very, very sudden, there has been no thorough preparation. But everything must be carried out so that the learning process continues to run smoothly and all students actively participate in learning even in the Covid-19 pandemic situation. Microsoft Office PowerPoint or PowerPoint is a computer program that is used for presentations, this application was developed by Microsoft in a package of office applications, namely Microsoft Office, in addition to Microsoft Word, Excel, Access and several other programs. PowerPoint runs on Microsoft Windows and Apple Macintosh for Apple Mac OS users, although initially this application runs on the Xenix operating system. PowerPoint has been widely used, especially in offices and business people, teachers, students, and trainers. His version continues to grow from the 2003 version of the Microsoft Office System, Microsoft changed the name from Microsoft PowerPoint alone to Microsoft Office PowerPoint. Then, in Office 2013, the name is simply abbreviated as PowerPoint and it continues to develop PowerPoint is version 15 and so on until now